Territory and Electoral Rules in Post-Communist Democracies - Bochsler, Daniel. author. aut Link
XIV, 215 p.
Keywords: The book extends research on the territorial structure of party systems (party nationalization) to 20 post-communist democracies. It explains party nationalisation as a consequence of ethnically oriented politics, and shows how party nationalisation can increase our understanding of electoral systems.